2004
DOI: 10.1007/s00464-003-9295-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the aldosterone receptor antagonist potassium canrenoate on renal blood flow and urinary output during prolonged increased intraabdominal pressure (IAP) in pigs

Abstract: Increased IAP in pigs is associated with markedly reduced urinary output and increased serum concentrations of aldosterone. Although the urinary output did not increase significantly, the increased sodium concentration in the urine of canrenoate-treated animals suggests that the high blood level of aldosterone contributes to the oliguria under increased IAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…We found that CA had little impact on either PRA or plasma Ang IIresults comparable to those reported by other investigators after acute MR antagonism, 25,33,34 and although a stimulatory effect of CA on renin secretion might have been anticipated secondary to the fall in arterial pressure, this may have been countered by the concomitant renin-inhibitory increase in sodium excretion. In contrast, Ucn2, both alone and in combination with CA, significantly reduced circulating levels of both PRA and Ang II.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that CA had little impact on either PRA or plasma Ang IIresults comparable to those reported by other investigators after acute MR antagonism, 25,33,34 and although a stimulatory effect of CA on renin secretion might have been anticipated secondary to the fall in arterial pressure, this may have been countered by the concomitant renin-inhibitory increase in sodium excretion. In contrast, Ucn2, both alone and in combination with CA, significantly reduced circulating levels of both PRA and Ang II.…”
Section: Discussionsupporting
confidence: 90%
“…35 Moreover, there is some evidence suggesting that the Ucns may antagonize Ang II production via suppression of ACE levels. 18 As noted by others investigating the short-term effects of MR antagonism, 25,34,36 CA in the present study was characterized by marked (>2-fold) increases in plasma aldosterone levels, indicating successful blockade of the MR throughout the experiment. Contrarily, Ucn2 induced a significant decline in circulating aldosterone that presumably reflects the coincident decreases in plasma Ang II and perhaps potassium levels, although the latter was not reduced in a sustained fashion (≤2 hours postinfusion) as were with both Ang II and aldosterone.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24][25][26] Several solutions have been raised to overcome the above deranged hemodynamic effects, including gasless surgery, substituting different gases for CO 2 , fluid overload, and various pharmacologic means. [27][28][29] A mechanical solution raised by Bickel involves using an intermittent sequential pneumatic compression (ISPC) device to improve venous return and cardiac function. 30,31 This device was shown to reverse the hemodynamic changes and the cardiac autonomic control, as well as the hepatic and renal (visceral) perfusion.…”
mentioning
confidence: 99%
“…Various pharmacological agents have been tested to combat oxidative stress, and some antioxidants and vasodilators have been shown to be successful in animal models78, 108, 109. Administration of dopamine and endothelin 1 antagonists greatly improved the portal circulation in rats subjected to carbon dioxide and helium insufflation, but oxidative stress markers were not measured109.…”
Section: Resultsmentioning
confidence: 99%